The views of social workers at Charlotte Maxeke Johannesburg academic hospital about what makes quality spervision - Wendy, Simunyu (My University, 2017)
The current qualitative study researched what social workers viewed as constituting quality supervision including what they felt is needed in a supervisor in order to provide adequate and effective supervision and for them to experience supervision as a valuable and positive experience. The research adopted an exploratory approach to its enquiry, using a sample of ten social workers. The results revealed characteristics of what constitute quality supervision, identifying the supervisory relationship as central. In addition, results showed the importance of supervision in social work practice by revealing that supervision increases professional growth and contributes to increased job performance, therefore recommendations to continuously promote quality supervision in social work practice were drawn from the findings of the study. Keywords: Supervision, Supervisory relationship, Administrative function of supervision, Educational function of supervision, Supportive function of supervision, Quality supervision.
A report on a study project presented to The Department of Social Work School of Human and Community Development Faculty of Humanities University of the Witwatersrand In partial fulfilment of requirements For the degree Bachelor of Social Work